1978
DOI: 10.1037/0012-1649.14.4.443
|View full text |Cite
|
Sign up to set email alerts
|

Adult age differences in remembering faces.

Abstract: Adult age differences in recognition memory for pictures of faces were assessed under different instructional conditions. The experiment was designed to test Eysenck's "processing-deficit" account of age differences in memory by varying the subject's encoding of the faces. Although older subjects recognized fewer faces, the elaborative orienting task facilitated recognition memory equally in two different adult age groups (18-25 years vs. 50-80 years). The processing-deficit hypothesis was not supported by thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
76
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 3 publications
15
76
1
Order By: Relevance
“…Faces, however, constitute an exception to this general finding of preserved picture recognition. In comparison with younger adults, older adults are significantly impaired in their recognition of unfamiliar faces (Bartlett, Leslie, Tubbs, & Fulton, 1989;Crook & Larrabee, 1992;Grady et al, 1995;Smith & Winograd, 1978). Moreover, neuroimaging studies of face perception and memory in older and younger adults have found different patterns of frontal and medio-temporal activation in older adults than in young (Grady, 2002;Grady et al, 1994;Grady et al, 1995).…”
mentioning
confidence: 97%
“…Faces, however, constitute an exception to this general finding of preserved picture recognition. In comparison with younger adults, older adults are significantly impaired in their recognition of unfamiliar faces (Bartlett, Leslie, Tubbs, & Fulton, 1989;Crook & Larrabee, 1992;Grady et al, 1995;Smith & Winograd, 1978). Moreover, neuroimaging studies of face perception and memory in older and younger adults have found different patterns of frontal and medio-temporal activation in older adults than in young (Grady, 2002;Grady et al, 1994;Grady et al, 1995).…”
mentioning
confidence: 97%
“…However, there are agerelated differences in the recognition of faces (Bartlett & Leslie, 1986;Bartlett, Leslie, Tubbs, & Fulton, 1989;Ferris, Crook, Clark, McCarthy, & Rae, 1980;Smith & Winograd, 1978). These differences show a characteristic pattern of near age-invariance in hits in response to old faces and an age-related increase in false alarms in response to new faces (Bartlett et al, 1989;Bartlett, Strater, & Fulton, 1991).…”
mentioning
confidence: 99%
“…Participants are shown a series of faces labeled with proper names, and later in the procedure they are presented with the original faces and asked to give the particular name that appeared with each face (e.g., Crook et al, 1993;Evrard, 2002). However, such a task does not definitely tell us whether the deficit that older adults show stems from their poorer memory for the components (i.e., the face or name; there are indications that recognition memory for faces declines in late life, e.g., see Bartlett, Leslie, Tubbs, & Fulton, 1989;Crook & Larrabee, 1992;Smith & Winograd, 1978) or from their difficulty in accessing the appropriate name given a face in a cued-recalltype task.…”
mentioning
confidence: 99%